1997
DOI: 10.1093/nar/25.24.5110
|View full text |Cite
|
Sign up to set email alerts
|

The proofreading domain of Escherichia coli DNA polymerase I and other DNA and/or RNA exonuclease domains

Abstract: Prior sequence analysis studies have suggested that bacterial ribonuclease (RNase) Ds comprise a complete domain that is found also in Homo sapiens polymyositis-scleroderma overlap syndrome 100 kDa autoantigen and Werner syndrome protein. This RNase D 3'-->5' exoribonuclease domain was predicted to have a structure and mechanism of action similar to the 3'-->5' exodeoxyibonuclease (proofreading) domain of DNA polymerases. Here, hidden Markov model (HMM) and phylogenetic studies have been used to identify and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
211
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(219 citation statements)
references
References 67 publications
8
211
0
Order By: Relevance
“…By using two-hybrid analysis, we have demonstrated that Pab1p interacts with Pan3p and Pbp1p, two proteins that respectively appear to act as positive and negative regulators of PAN activity (9,23). Not surprisingly, our experiments have also shown that these two proteins also interact with the Pan2p subunit of PAN, i.e., the subunit whose homologies to previously characterized exonucleases (8,26) suggest that it harbors the catalytic activity relevant to PAN function. Figure 9 summarizes this set of interactions and raises interesting possibilities for the precise role of Pab1p in poly(A) trimming.…”
Section: Discussionsupporting
confidence: 61%
“…By using two-hybrid analysis, we have demonstrated that Pab1p interacts with Pan3p and Pbp1p, two proteins that respectively appear to act as positive and negative regulators of PAN activity (9,23). Not surprisingly, our experiments have also shown that these two proteins also interact with the Pan2p subunit of PAN, i.e., the subunit whose homologies to previously characterized exonucleases (8,26) suggest that it harbors the catalytic activity relevant to PAN function. Figure 9 summarizes this set of interactions and raises interesting possibilities for the precise role of Pab1p in poly(A) trimming.…”
Section: Discussionsupporting
confidence: 61%
“…The T. gondii XPMC2 (TgXPMC2) cDNA encodes a protein of 361 amino acids with a predicted molecular weight of ª40 kDa and an isoelectric point of 9.59 (accession number AY841997). The N-terminal half of the protein encodes a putative exonuclease domain (residues 60-219) conserved in all XPMC2-related genes (Moser et al, 1997) (Fig. 3).…”
Section: Genetic Rescue Of Cell Cycle Mutant Ts 11c9mentioning
confidence: 99%
“…Higher eukaryotes also contain the PARN deadenylase, which is a principle component of cell-free extracts capable of efficient poly(A) shortening (15). Both PAN2 and PARN are members of the DEDD family of RNases (16,17). PAN2 is specifically activated by the poly(A)-binding protein (PAB1), whereas PARN becomes activated in the presence of the mRNA cap structure (15).…”
mentioning
confidence: 99%